BIBLIOMETRIC COMPUTATIONAL MAPPING ANALYSIS OF PUBLICATIONS ON FERROUS FERRIC OXIDE (Fe3O4) NANOPARTICLES USING VOSVIEWER - Anisa Noorlela; Asep Bayu Dani Nandiyanto (Journal of Mechanical Engineering, Science, and Innovation, 2022)
This study aims to analyze computational bibliometric mapping using VOSviewer software on Fe3O4 nanoparticles. The article data was obtained from the Google Scholar database using a reference manager application, namely Publish or Perish. Publish or Perish software is used to conduct a literature review on the selected topic. The title and abstract of the article are used to guide the search process by referring to the keyword “Fe3O4 nanoparticles”. It was found that 998 articles related to the research period used as study material were Google Scholar indexed articles for the last 10 years (2012 to 2022). The results show that Fe3O4 nanoparticles research can be separated into 3 terms: Fe3O4 nanoparticles, nanoparticles, and Fe3O4. The term " Fe3O4 nanoparticles" is associated with 217 links with a total link strength of 986. The term "Nanoparticles" has 259 links with a total link strength of 1667 and the term " Fe3O4" has 237 links with a total link strength of 1297. The results of the analysis of research developments related to Fe3O4 nanoparticles fluctuated from 2012 to 2019. The largest increase in publications was in 2017 and 2018 with the number of publications being 110 and 109. In the last 3 years there has been a drastic decline, namely in 2020 as many as 96 publications, 2021 as many as 73 publications, and 2022 as many as 27 publications. These data indicate that the popularity of Fe3O4 nanoparticle research is relatively unstable and interest in Fe3O4 nanoparticles has decreased. This study examines how many articles have been published on Fe3O4 nanoparticles and their relation to problem areas using VOSviewer. This review of the article can serve as a starting point for research related to other materials.